Dynamic remodeling of arteriolar collaterals after acute occlusion in chick chorioallantoic membrane. (May 2017) - Xiang, Weiwei; Reglin, Bettina; Nitzsche, Bianca; Maibier, Martin; Rong, Wen Wei; Hoffmann, Björn; Ruggeri, Alfredo; Guimarães, Pedro; Secomb, Timothy W.; Pries, Axel R.
ABSTRACT: Objective: After arteriolar occlusion, collaterals enlarge and initially elevated WSS normalizes. While most previous studies focused on endpoints of such adaptive changes in larger collaterals, the present investigation aimed to continuously determine the relation between WSS and diameter in microvascular collaterals during adaptive reactions. Methods: In Hamburger‐Hamilton stage 40 CAMs, junction points between arteriolar segments were identified and the third upstream segment on one side was occluded. Intravital microscopy recordings were taken for 24 hours post‐occlusion. Segment diameter and blood velocity were measured: WSS and capillary density were calculated. Results: After occlusion, vascular diameters exhibited an immediate decrease, then increased with a time constant of 2.5 ± 0.8 hours and reached a plateau of up to 60% above baseline after about 7 hours. Vascular tone showed no significant change. WSS exhibited an immediate increase post‐occlusion and linearly returned to baseline after about 12 hours. Local WSS change and diameter change rate showed similar patterns during the initial but not the later phase of post‐occlusive adaptation. Conclusions: CAM collaterals undergo fast structural remodeling within 24 hours post‐occlusion. This remodeling might be driven by local WSS and by other regulators within the vascular network.